The EMF: concluding remarks - THYGESEN, N. (PSL Quarterly Review, 2013)
The European Monetary Fund was the subject of the Second International Seminar on European Economic and Monetary Union, held in Geneva in December of 1979. In these concluding remarks, the author summarises some of the main points of discussion and offers some further considerations. JEL: F33, F36